Development of vending machine with prepaid payment method - Amar Safuan, Alyusi (2008)
Vending machine is a coin operated machine for selling various products. There were some problem occur in the payment problem method. The payment cannot be accepted and stuck, also cannot get the product is the major problem for the payment method. So for the problem, new payment system was introduced which is using prepaid method. The objectives in this project are developing a vending machine and then insert a new payment method proposed into it. The system builds using plunger as a new design that insert into each funnel in vending machine. The plunger control by circuit that been built using parallel port and attached to the computer. The programming for parallel port was using C as language. The body for this vending machine was developing using acrylic which is material that cannot rust. The completed vending machine develops in this project will be using a PC as a guide to connect into the vending machine. The customers need to insert right code to use the vending machine. The product will be released regarding to the customer chosen. If wrong, the customer cannot use the vending machine.